DISSECTING THE ROLE OF MAJOR YIELD CONTRIBUTING TRAITS IN FINAL YIELD POTENTIAL IN RICE HYBRID - JAVED, HM; IJAZ, M; SABAR, M; KHAN, SU; SHAMIM, F; KHAN, NH; AZIZ, S; ARIF, M; KHALIQ, A; ASLAM, M; et al. (Biological and Clinical Sciences Research Journal, 2024)
Rice is the second most important crop which feeds almost half of the population on this globe. It is widely cultivated in all parts of the world and has special importance in Asia and Africa. Currently, all agronomic crops including rice are being affected adversely by changes induced by global warming in almost all parts of the world. There is a need to find new ways to tackle these door-threatening issues which will complex the situation further soon. Genetic improvements in plants with better trait profiles for high yields and resilience towards climatic conditions offer a flexible and permanent solution in such situations. This study was carried out at Rice Research Institute, Kala Shah Kaku to dissect the contributing role of some major plant traits like no of tillers per plant, no of grains per panicle, and grain weight in rice hybrid plant yield. Results showed that all these traits add their part positively to the final yield potential in such a way that no of tillers per plant comes at 1st with an optimum value of 15 tillers per plant. It has its yield-enhancing role individually as well as collectively with two other traits. Grain number per panicle boosted yield in rice hybrids when fixed at 186 while thousand-grain weight with a value of 30 g was the best option to increase yield and productivity in rice. Negative individual coefficients of all these traits were estimated while positive coefficients with a high contribution towards yield were observed for combined effects of tillers per plant along with no of grains per panicle and grain weight. These findings will assist the researcher in the selection of criteria crops especially improvements in rice hybrids.